Remuneration Model for Health Workers in A State University Hospital (Case Study at The University of Indonesia Hospital) - Dini Trisnowati; Asropi Asropi; Edy Sutrisno (Quantitative Economics and Management Studies, 2024)
A high turn over rate is an indicator for a company to implement a strategy to retain employees. From the literature study, it was found that one of the efforts to retain employees is through compensation strategies. Compensation can be used as an attraction to attract prospective employees with high qualifications and retain high performing employees. The role of state university hospitals (RSPTN) as places for education, research and integrated health services in the fields of medical and/or dental education, continuing education and other health education in a multi-professional manner cannot be separated from the role of existing health workers. This research is to look for components that can be taken into account as remuneration components to obtain a remuneration model for health workers at RSPTN.